PENGARUH ATRAKTOR RUMPON TERHADAP HASIL TANGKAPAN ALAT TANGKAP BAGAN (LIFT NET) DI PERAIRAN DEMAK - Bogi B Jayanto; Asriyanto .; A. Rosyid; H. Boesono (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
One  kind  of  fishing  gear  that  use  to  captured  phototaxis  positif  fish  is  Lift  Net.  Lamp  was  no longer  used  as  fish  aggregating  device  for  lift  net  because  it  was  uneffective  and  unefficient  to gathered  fish  target.  If  the  problem  still  continued  it  can  raised  fuels  consumption  for  lamp attractor. Another fish aggregating device “rumpon” was a solution for lift net operation. Research objectives were to increase effectivity, efficiency and fishing production, and hopefully it can raise fisheries income.  Keyword : Liftnet, Rumpon, Demak Seawaters